Reputation and certification in online shops - Franz Hackl; Agnes Kügler; Rudolf Winter-Ebmer (Institute for Advanced Studies (IHS), 2011)
We investigate the impact of self-organized reputation versus certification by an independent institution on demand for online shops. Using data from a large Austrian price comparison site, we show that quality seals issued by a credible and independent institution increase demand more than feedback-based reputation. This result is important for markets where the market-maker must deal with issues of asymmetric information concerning the quality of goods and services in the market.
Keywords: C23; D21; D81; L15; 330; online markets; search engines; signaling; certification; reputation